УБАВИНАТА НА ИДЕИТЕ (Filološke pripombe, 2019)
The basic principle of the hermeneutic approach is summarized in the exclamation: Back to the work! The lock of the hermeneutic approach key is the text, and how to put and to keep the text in the foreground but not the apriori evaluations, all alone and independent from the work. The hermeneutic approach is focused on a single target: to interpret and to present the text of a novel, or of a poem, by means of the novel itself, or the poem itself. In the hermeneutic approach the work is disclosed authentically by itself. The hermeneutic criticism is based on an interpretation of the work, but an interpretation which includes its philosophical position. The immanent interpretation of the text presents a hermeneutic reconstruction of all layers in the literary work, which, mediating between philosophy and literature, searches for its metaphysical qualities because they give to the work a lasting meaning and depth at the most.